Kejelasan Sasaran, Pelaksanaan Anggaran, dan Regulasi Terhadap Penyerapan Anggaran dengan Komitmen Organisasi Sebagai Pemoderasi - Rahmawati Rahmawati; Khristina Yunita; Muhsin Muhsin; Rusliyawati Rusliyawati; Angga P. Karpriana (CV. Ulil Albab Corp, 2024)
The purpose of this study was to determine the effect of target clarity, budget implementation and regulations on budget absorption with organizational commitment as a moderator. This research uses quantitative methods and uses primary data. Determining the number of samples in this study used saturated samples. The population in this study was 81 employees, so the sample used was 81 employees. Research hypothesis testing was carried out using the Structural Equation Model (SEM) approach using Smart Partial Least Square (PLS) software version 3.0. The research results show that clarity of targets and budget implementation have a significant effect on budget absorption. Regulations do not have a significant effect on budget absorption. As well as clarity of targets, budget implementation and regulations with organizational commitment have a significant effect on budget absorption.